2011
DOI: 10.1371/journal.pone.0029593
|View full text |Cite|
|
Sign up to set email alerts
|

Increase in Diarrheal Disease Associated with Arsenic Mitigation in Bangladesh

Abstract: BackgroundMillions of households throughout Bangladesh have been exposed to high levels of arsenic (As) causing various deadly diseases by drinking groundwater from shallow tubewells for the past 30 years. Well testing has been the most effective form of mitigation because it has induced massive switching from tubewells that are high (>50 µg/L) in As to neighboring wells that are low in As. A recent study has shown, however, that shallow low-As wells are more likely to be contaminated with the fecal indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…Our results are generally consistent with the prior version of this Cochrane Review (Clasen 2006) and with other reviews of water quality interventions (Fewtrell 2005; Arnold 2007; Waddington 2009; Cairncross 2010; Wolf 2014). …”
Section: Discussionsupporting
confidence: 88%
“…Our results are generally consistent with the prior version of this Cochrane Review (Clasen 2006) and with other reviews of water quality interventions (Fewtrell 2005; Arnold 2007; Waddington 2009; Cairncross 2010; Wolf 2014). …”
Section: Discussionsupporting
confidence: 88%
“…The combined effects can still be important for fecal contamination of groundwater even it is not synergistic. Our results, together with others, 17, 3740 provide useful information for identifying risk factors for fecal contamination of groundwater and finding safe drinking water resources. Bangladesh is extremely vulnerable to climate change.…”
Section: Discussionsupporting
confidence: 72%
“…The majority of villagers obtain their drinking water from shallow tube wells in sand aquifers so at least part of the high level of diarrheal disease might be attributable to exposure to fecal-contaminated well water 22-24 . Two recent studies observed frequent occurrence of the fecal indicator bacterium (FIB) E. coli in tube-well water, particularly during the monsoon 18,23 .…”
Section: Introductionmentioning
confidence: 99%